2001
DOI: 10.1046/j.1460-9568.2001.01373.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential targeting of components of the dystrophin complex to the postsynaptic membrane

Abstract: Accumulating evidence points to the participation of dystroglycan in the clustering of nicotinic acetylcholine receptors at the neuromuscular junction [Côté et al. (1999) Nature Genet., 3, 338--342]. Dystroglycan is part of a multimolecular complex, either associated with dystrophin (the dystrophin-associated protein complex) at the sarcolemma or with utrophin (the utrophin-associated protein complex) at the neuromuscular junction. Understanding the assembly of this complex at the developing synapse led us to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 62 publications
4
23
0
Order By: Relevance
“…It has been proposed that rapsyn and AChRs are co-transported through the secretory pathway to the postsynaptic apparatus in Torpedo electrocytes (20,31). This, together with our observed intracellular rapsyn-AChR complexes (Fig.…”
Section: Neural Agrin Increases the Interaction Of Rapsyn With The Acsupporting
confidence: 86%
“…It has been proposed that rapsyn and AChRs are co-transported through the secretory pathway to the postsynaptic apparatus in Torpedo electrocytes (20,31). This, together with our observed intracellular rapsyn-AChR complexes (Fig.…”
Section: Neural Agrin Increases the Interaction Of Rapsyn With The Acsupporting
confidence: 86%
“…The notion that GlyR could associate with gephyrin as it is transported from the TGN to the plasma membrane is comparable with that of the association of rapsyn and components of the dystrophin-associated complex with AChR, as suggested by their colocalization in post-Golgi vesicles (Marchand et al, 2000(Marchand et al, , 2001. Although the direct association of these molecules with intracellular AChR was not demonstrated, these reports support the notion that elements of the neuromuscular junction are delivered to the plasma membrane as preassembled complexes .…”
Section: Toward a Preconstruction Of The Postsynaptic Membranessupporting
confidence: 66%
“…The intracellular accumulation of the syntrophins suggests that these proteins are targeted to the muscle membrane via a different mechanism than that used by the rest of the DAPC. Indeed, previous work has indeed shown that dystrophin and syntrophin take different routes during targeting to the membrane (32). Syntrophins are transported in post-Golgi vesicles that exocytose to fuse with the membrane, while dystrophin becomes directly associated with the sarcolemma following synthesis.…”
Section: Discussionmentioning
confidence: 99%